Violence suffered by Venezuelan immigrant female sex workers: an intersectional view - Arruda-Barbosa, Loeste de; Menegatti, Mariana Sbeghen; Fonseca, Rosa Maria Godoy Serpa da; Oliveira, Maria Amélia de Campos (Revista da Escola de Enfermagem da U S P, 2024)
ABSTRACT Objective: To characterize and analyze violence committed against Venezuelan immigrant female sex workers, from the perspective of an intersectional look at social class, gender and race-ethnicity. Method: Exploratory study with a qualitative approach. Data sources: interviews with 15 Venezuelan immigrant women sex workers and 37 Brazilian online media reports that addressed the topic. Data were submitted to thematic content analysis, with the support of Qualitative Data Analysis (WebQDA) software. Results: Thematic analysis of data from reports and interviews allowed the emergence of three empirical categories: Structural violence and reasons that led to prostitution: a question of social class; Among the forms of violence, the most feared: physical violence; Violence based on gender and race-ethnicity. Conclusion: The study made it possible to recognize that Venezuelan immigrant women who are sex workers in Brazil are subject to different types of violence and exploitation. This scenario is due to a reality of life and work that is based on the exploitation of female workers who experience the consequences of the interweaving of subalternities characteristic of their social insertion of class, gender and race-ethnicity. RESUMEN Objetivo: Caracterizar y analizar la violencia ejercida contra trabajadoras sexuales inmigrantes venezolanas, desde una mirada interseccional de clase social, género y raza-etnia. Método: Estudio exploratorio con enfoque cualitativo. Fuentes de datos: entrevistas con 15 trabajadoras sexuales inmigrantes venezolanas y 37 informes de medios en línea brasileños que abordaron el tema. Los datos fueron sometidos al análisis de contenido temático, con el apoyo del software Qualitative Data Analysis (WebQDA). Resultados: El análisis temático de los datos de los informes y entrevistas permitió la emergencia de tres categorías empíricas: Violencia estructural y motivos que llevaron a la prostitución: una cuestión de clase social; Entre las formas de violencia, las más temidas: la violencia física; Violencia basada en el género y la raza-etnia. Conclusión: El estudio permitió reconocer que las mujeres inmigrantes venezolanas que ejercen el trabajo sexual en Brasil están sujetas a diferentes tipos de violencia y explotación. Este escenario obedece a una realidad de vida y de trabajo que se fundamenta en la explotación de los trabajadores que experimentan las consecuencias del entrecruzamiento de subalternidades propias de su inserción social de clase, género y raza-etnia. RESUMO Objetivo: Caracterizar e analisar violências praticadas contra mulheres imigrantes venezuelanas profissionais do sexo, na perspectiva de um olhar interseccional de classe social, gênero e raça-etnia. Método: Estudo exploratório de abordagem qualitativa. Fontes dos dados: entrevistas com 15 mulheres imigrantes venezuelanas trabalhadoras do sexo e 37 reportagens da mídia online brasileira que abordavam o tema. Os dados foram submetidos à análise de conteúdo temática, com o apoio do software Qualitative Data Analysis (WebQDA). Resultados: A análise temática dos dados das reportagens e das entrevistas permitiu a emergência de três categorias empíricas: Violência estrutural e motivos que levaram à prostituição: uma questão de classe social; Entre as violências, a mais temida: a violência física; Violências baseadas no gênero e na raça-etnia. Conclusão: O estudo permitiu reconhecer que mulheres imigrantes venezuelanas profissionais do sexo no Brasil estão sujeitas a diferentes tipos de violência e exploração. Este cenário deve-se a uma realidade de vida e trabalho que se fundamenta na exploração de trabalhadoras que vivenciam as consequências do entrelaçamento das subalternizações características da sua inserção social de classe, gênero e raça-etnia.